Moving to a new dimension: 3D kidney cultures for kidney regeneration. (June 2022) - Namestnikov, Michael; Dekel, Benjamin
Abstract: In recent years, it has become apparent that 3D cultures of kidney cells may help maintain cells' heterogeneity and in vivo phenotypes crucial for disease modelling and drug discovery by mimicking tissue-specific cell–cell contact and microarchitecture. Kidney spheroids, organoids, and tubuloids have been described with different cell sources utilized to establish the 3D kidney cultures, with natural in vivo processes instructing ex vivo growth; in fetal life, a developmental hierarchy exists with nephron progenitors giving rise to developing kidney epithelia and whole nephrons while in adult life mature clonal renal cells act within existing nephrons as lineage-restricted segment-specific progenitors for local regeneration. Importantly, for regenerative purposes expansion of isolated renal cells that harbor renal structure forming potential is required. Accordingly, we showed that redifferentiation of 2D proliferating adult kidney cells as 3D spheroids, reverts a pro-inflammatory, pro-fibrotic program leading to enhanced renal potency and improved engraftment as self-organizing renal structures. This review summarizes the use of 3D culture methods of kidney cells with emphasis on the derivation of spheroids from different cell sources and their potential for kidney bioengineering and therapeutic regeneration.